Airline brand management: a practical perspective to brand management in the airline industry - Sezgen, Eren; Mason, Keith J.; Mayer, Robert (Elsevier, 2023)
Measuring and managing airline services cannot be easily achieved using the tools developed to measure brands in goods and most other services industries due to some unique characteristics of the airline industry. This paper seeks to explain airline branding, brand management, and brand measurement from the perspective of airline marketing professionals. The aim is to identify customer-based brand equity (CBBE) measures appropriate to the unique nature of the airline industry. Furthermore, we explore the dimensions that drive brand equity in the airline industry. The paper uses semi-structured expert interviews to collect data from senior marketing executives working for both full-service and low-cost carriers, in addition to airline branding/marketing consultants. The findings reveal the factors that drive airline customer-based brand equity (CBBE) as awareness, functional and technical service performance, credibility, differentiation, value, satisfaction, and loyalty. The research encapsulates the basic dimensions of brand equity advocated in the branding literature but also some measures which are new to the airline branding literature (functional and technical service performance, and credibility). These measures are critical for airline managers as they attempt to build equity in their respective brands. Therefore, this research offers researchers and practitioners a better understanding of brand equity measurement and of brand equity formation for airlines.
Keywords: Airline; Brand; Customer; Brand equity